Morbidity and trends in length of hospitalisation of very and extremely preterm infants born between 2008 and 2021 in the Netherlands: a cohort study - Floris Groenendaal; Kees Ahaus; Karen de Bijl-Marcus; Manon J N L Benders; Jeroen Dudink; Marijn Kahlmann (BMJ Open)
Objectives This study investigated changes in the length of stay (LoS) at a level III/IV neonatal intensive care unit (NICU) and level II neonatology departments until discharge home for very preterm infants and identified factors influencing these trends.Design Retrospective cohort study based on data recorded in the Netherlands Perinatal Registry between 2008 and 2021.Setting A single level III/IV NICU and multiple level II neonatology departments in the Netherlands.Participants NICU-admitted infants (n=2646) with a gestational age (GA) <32 weeks.Main outcome measures LoS at the NICU and overall LoS until discharge home.Results The results showed an increase of 5.1 days (95% CI 2.2 to 8, p<0.001) in overall LoS in period 3 after accounting for confounding variables. This increase was primarily driven by extended LoS at level II hospitals, while LoS at the NICU remained stable. The study also indicated a strong association between severe complications of preterm birth and LoS. Treatment of infants with a lower GA and more (severe) complications (such as severe retinopathy of prematurity) during the more recent periods may have increased LoS.Conclusion The findings of this study highlight the increasing overall LoS for very preterm infants. LoS of very preterm infants is presumably influenced by the occurrence of complications of preterm birth, which are more frequent in infants at a lower gestational age.